L. Quincy Mumford papers - Mumford, L. Quincy (Lawrence Quincy), 1903-1982.
Correspondence, writings, reports, bibliographical material, committee reports, congressional bills, newspaper clippings, photographs, and other papers relating to Mumford's career at the Library of Congress.
Librarian of Congress.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection related to the Library of Congress Archives.
Certificates formerly cataloged as part of the Miscellaneous Manuscripts collection transferred to the L. Quincy Mumford papers.
Keywords: Library of Congress; Library of Congress -- Officials and employees; Libraries -- Washington (D.C.); Librarians of Congress